A web-based intervention to promote applications for rehabilitation: a study protocol for a randomized controlled trial. Issue 1 (December 2015) - Spanier, Katja; Streibelt, Marco; Ünalan, Firat; Bethge, Matthias
Abstract Background The German welfare system follows the principle "rehabilitation rather than pension, " but more than the half of all disability pensioners did not utilize medical rehabilitation before their early retirement. A major barrier is the application procedure. Lack of information about the opportunity to utilize rehabilitation services restricts the chance to improve work ability and to prevent health-related early retirement by rehabilitation programs. The establishment of new access paths to medical rehabilitation services was, therefore, identified as a major challenge for rehabilitation research in a recent expertise. Thus, a web-based information guide was developed to support the application for a medical rehabilitation program. Methods/Design For this study, the development of a web-based information guide was based on the health action process approach. Four modules were established. Three modules support forming an intention by strengthening risk perception (module 1), positive outcome expectancies (module 2) and self-efficacy (module 3). A fourth module aims at the realization of actual behavior by offering instructions on how to plan and to push the application process. The study on the effectiveness of the web-based information guide will be performed as a randomized controlled trial. Persons aged 40 to 59 years with prior sick leave benefits during the preceding year will be included. A sample of 16, 000 persons will be randomly drawn from the registers of 3 pension insurance agencies. These persons will receive a questionnaire to determine baseline characteristics. Respondents of this first survey will be randomly allocated either to the intervention or the control group. Both study groups will then receive letters with general information about rehabilitation. The intervention group will additionally receive a link to the web-based information guide. After 1 year, a second survey will be conducted. Additionally, administrative data will be used to determine if participants apply for rehabilitation and finally start a rehabilitation program. The primary outcomes are the proportion of applied and utilized medical rehabilitation services. Secondary outcomes are cognitions on rehabilitation, self-rated work ability, health-related quality of life and perceived disability, as well as days with sick leave benefits and days of regular employment. Discussion The randomized controlled trial will provide highest ranked evidence to clarify whether theory-driven web-based information supports access to rehabilitation services for people with prior sickness benefits. Trial registration German Clinical Trials Register (Identifier:DRKS00005658, 16 January 2014).